Effects of alpha-tocopherol and oleic acid content in sunflower oil subjected to discontinuous and prolonged frying process - Manzo, Nadia; Santini, Antonello; Pizzolongo, Fabiana; Aiello, Alessandra; Romano, Raffaele (Progress in Nutrition, 2019)
Frying is a widespread cooking method that positively influences the sensory characteristics of food. Despite the advantages, physical and chemical changes leading to oil degradation can occur. The presence of antioxidants, such as α-tocopherol, and a reduced content of polyunsaturated fatty acids are reported in the scientific literature as factors reducing oxidation processes. The aim of this study was to compare the effects of α-tocopherol addition and the presence of a high concentration of oleic acid in sunflower oil subjected to a prolonged and discontinuous frying process. Every 8 hours of process, the following determinations were performed on oils: free fatty acids (FFA), peroxides value (PV), fatty acids composition (FA), total polar compounds (TPC). High oleic sunflower oil showed the best frying performance, with lower total polar compounds, lower octanoic acid formation and a lower unsaturated/saturated fatty acids (UFA)/(SFA) ratio decrease than oil to which α-tocopherol was added. These results showed that the presence of monounsaturated fatty acids may largely influence the heat resistance of sunflower oil more than the presence of α-tocopherol.